Visuospatial working memory, auditory discrimination, and attention. Issue 4 (21st April 2019) - Shipstead, Zach; Martin, Jessie D.; Nespodzany, Ashley
ABSTRACT: The present study examined the degree to which tests of visuospatial storage capacity tap into domain-general storage and attention processes. This was done by comparing performance of visuospatial memory tasks with performance on sound-based sensory discrimination tasks. We found that memory task- and discrimination task performance both tapped into a cross-modality factor (visual and auditory). We further examined the degree to which this common variance could be explained by attention control and sustained attention. These attention factors accounted for roughly 60% of the variance in memory. This indicates that tests of visuospatial memory capacity reflect more than modality-specific memory.